A Brief Evaluation on ISSI 2015 - Umut Al (Türk Kütüphaneciliği)
The purpose of this paper is to briefly evaluate and to give some information about the 15th International Society of Scientometrics and Informetrics (ISSI 2015), which was held in Boğaziçi University on June 29 - July 4, 2015.  ISSI 2015 hosted more than 300 participants and it is pleasing that large number of audiences have shown interest in the Conference. 54% of the full papers and research in progress papers and 66% of the posters and ignite talks were accepted to be presented in the Conference. When the countries of the researchers that were contributed to the Conference were examined, it was realized that people from Republic of China, The United States of America, Canada, Spain and The Netherlands were in the top of the list in terms of the number of contributions. Selected papers will be published in Scientometrics which is an ISSI 2015 special issue. The next International Society of Scientometrics and Informetrics Conference will be held in Wuhan, People’s Republic of China, in 2017.